ANALYSIS OF FINANCIAL RATIOS IN THE SECTOR PALM OIL AGRICULTURE AT PT. SINAR MAS AGRO RESOURCE AND TECHNOLOGY TBK (SMART) - Lusi Afriliana; Melisa; Riska Yanti; Salsabila (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Financial ratios are analytical tools used to measure and evaluate a company's financial performance. These ratios are calculated based on data contained in financial reports, such as balance sheets, income statements, and cash flow statements. Financial ratios provide important information about certain aspects of corporate finance, such as profitability, liquidity, efficiency, and solvency. In the financial world, financial ratios are an important tool for evaluating a company's performance and financial health. This financial ratio is calculated based on the data and components contained in the company's financial statements.With Using financial ratios, we can assess company performance internally, compare company performance between certain time periods, and make comparisons with other companies in the same industry.